The Local Government and Creative Industry: Experience from Batik Tulis Lasem Industries - Roziqin, Ali; Retnandari, Nunuk; Fajrina, Amaliana; Sihidi, Iradhad; Kamil, Muhammad (Research and Development Agency Ministry of Home Affairs, 2021)
Recently, Batik Tulis Lasem had several problems with a product, starting from input until the market process. Also, there is the problem of capital and technological capabilities from Batik Tulis Lasem industry, poverty, and social inequality of the craftsman. This article aims to examine the role of local government in improving creative industries, especially Batik Tulis Lasem. Further, this article was conducted by qualitative descriptive approach, particularly using the case study. In addition, the researchers collected data from semi-structured interviews with official local government and Batik Tulis Lasem entrepreneurs in the period covered 2018-2019. The results showed that local government has an important role in improving creative industries, firstly as a regulator, secondly as a facilitator, and thirdly to ensure the existence of Batik Tulis Lasem through empowerment. The problems in Batik Tulis Lasem are the regeneration of entrepreneurs, including batik craftsman, the lack of empowerment by local government, and the lack of information technology knowledge among the majority of Batik entrepreneurs. As an implication, the government should increase empowerment for the Batik Tulis Lasem industry through the regeneration program of batik craftsman and increase capacity for digital marketing.